Voices of Teachers on School Violence and Gender in South African Urban Public Schools - Netshitangan, Tshilidzi (Journal of Reviews on Global Economics, 2019)
This article discusses the findings of a study conducted in Gauteng, South Africa. The main aim of the study was to examine how principals and educators experience and address violence in schools. This included investigating the gendered nature of school violence. The study used a qualitative research method, which drew upon individual and focus group interviews to collect data from the School Management Teams (SMTs), educators and the School Governing Bodies (SGBs parent component). Using a post-structural feminist view to understand the gendered nature of violence in the schools, the research findings show that school violence is a male and female phenomenon, although boys (young males) were seen as the main protagonists of school violence. Findings also revealed that, although female educators are sometimes victims of school violence, they use violence reduction strategies in their professional capacity as educators that any other professional could apply regardless of their gender. The strategies for eliminating violence in schools should not be gendered but should rather be all-encompassing and should take all factors into account that may play a role in causing violence.